An In Vitro Comparison of Coronal Microleakage of Three Orifice Barriers Filling Materials - Hamidreza Yavari; Mohammad Samiei; Mahsa Eskandarinezhad; Shahriar Shahi; Marzieh Aghazadeh; Yones Pasvey (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
Introduction: A coronal barrier in root-filled teeth is one of the most effective methods for prevention of coronal microleakage. The aim of this study was to compare coronal microleakage of three materials [light-cured glass-ionomer (GI), mineral trioxide aggregate (MTA), and composite resin] as coronal barriers. Materials and Methods: A total of 188 intact maxillary incisors were used. After instrumentation, all the canals were obturated with gutta-percha and lateral condensation technique using AH26 sealer. Then, the teeth were sectioned just apical to the cemento-enamel junction. The roots were randomly assigned to three experimental groups (n=56) and two negative and positive control groups (n=20). After placing the orifice barrier, the samples were immersed in 2% methylene blue solution for 2 weeks at 37°C. Then the teeth were longitudinally sectioned mesiodistally and dye penetration was measured under a stereomicroscope at ×10 magnification. Data were analyzed with one-way ANOVA and a post-hoc Tukey test. Results: The positive control group leaked significantly more than all the experimental groups (P=0.001). MTA exhibited less leakage than composite and GI (P=0.002) but no significant differences were found between GI and composite groups. Conclusion: Immediate placement of a suitable intra-orifice barrier like MTA, before final restoration, may help minimize recontamination of the remaining apical gutta-percha.